Understanding of National Kabaddi Rules Among Central Java POMNAS Athletes 2025 - David Prayitno; Dias Fajar Widya Permana (Universitas Negeri Semarang, 2026)
This study aims to analyze the level of understanding of Central Java Kabaddi athletes to the rules of the National Style number match at the 2025 POMNAS. The study used a descriptive quantitative approach with a total sampling technique, involving 24 athletes as respondents. The research instrument is in the form of a five-level Likert scale structured questionnaire prepared based on the official regulations of the International Kabaddi Federation (IKF). The data was analyzed using descriptive statistical techniques in the form of percentages. The results showed that the level of athlete understanding was in the good category with a percentage of 81.53%. Most of the athletes are in the good and very good category, although there are still a small number in the fair category. These findings show that athletes have an adequate understanding of the rules of the game, both from technical and non-technical aspects, but are not optimally evenly distributed. Based on these results, it can be concluded that the level of understanding of Central Java Kabaddi athletes towards the rules of the National Style number match is in the good category, so efforts are needed to improve through more systematic socialization and coaching to achieve a more optimal level of understanding.